Immune Response against Hepatitis B Virus after Vaccination among Low Birth Weight and Preterm Newborns: A Retrospective Cohort Study in Magelang District Central Java - Muhardison Muhardison; Hari Kusnanto; Nenny Sri Mulyani (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Hepatitis B virus (HBV) infection is a major cause of morbidity and mortality in the world. Over 2 billion people are infected with HBV and 378 million are carriers. The mortality rate is approximately 1-2 million and over 4 millions acute clinical cases are documented each year. The prevalence of HBV infection in Indonesia is 3-20%. Vertical and horizontal transmission in newborn and children occurs in 25-45%. Near 25-50% of children are infected before 5 years. The most effective approach to reduce the burden of HBV infection is mass vaccination of newborns and children.Objectives: To determine immune response against HBV after HBV vaccine among low birth weight (LBW) and preterm newborns after HBV vaccination, and factors related to the immune response i.e. gender and weight gain in the first 6 months of life.Methods: During May-July 2012, 106 infants aged 13-15 months were recruited after HBV vaccination. They were completed 4 doses of HBV basic vaccination in 0, 2, 3, and 4 months of life. Sera were examined for anti-HBs antibody titers using ELISA.Results: A total of 98 subjects (92.5%) completed the study. Immune response of LBW subjects were positive in 89.7%, newborns were 95.9%. The Relative Risk (RR) were 2.5 CI (0.50 to 12.2) p=0.2178. Gender was not related to immune response RR 0.6 CI (0.15 to 2.69) p=0.6996. Gestational age associated with immune response RR 8 CI (1.05 to 63.9) p=0.0399. The first 6 months weight was not related to immune response RR 3.6 CI (0.73 to 17.7) p=0.1178. Logistic regression analysis showed LBW was not correlated with the immune response OR 1 CI (0.16 to 7.17) p=0.929. Gestational age correlated with immune response OR 9 CI (1.05 to 79.3) p=0.044 and the first 6 months of weight was not correlated with immune response OR 3.7 CI (0.65 to 21.1) p=0.138.Conclusion: Immune response against HBV after vaccination was similar between LBW and NBW. Immune response was correlated with gestational age.Keywords: Hepatitis B vaccine, immune response, LBW and preterm.